2007
DOI: 10.1161/01.atv.0000249861.80471.96
|View full text |Cite
|
Sign up to set email alerts
|

MEK–ERK Inhibition Corrects the Defect in VLDL Assembly in HepG2 Cells

Abstract: Objective-Hepatic VLDL assembly is defective in HepG2 cells, resulting in the secretion of immature triglyceride-poor LDL-sized apoB particles. We investigated the mechanisms underlying defective VLDL assembly in HepG2 and have obtained evidence implicating the MEK-ERK pathway. Methods and Results-HepG2 cells exhibited considerably higher levels of the ERK1/2 mass and activity compared with primary hepatocytes. Inhibition of ERK1/2 using the MEK1/MEK2 inhibitor, U0126 (but not the inactive analogue) led to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 43 publications
(47 reference statements)
7
55
0
Order By: Relevance
“…ERK has already been shown to be induced by MCP-1 in Chinese hamster ovary cells and in smooth muscle cells 22 , and to be involved in MCP-1-mediated monocyte chemotaxis. 34 Interestingly, Tsai et al 21 have recently demonstrated that inhibition of ERK pathway in HepG2 cells led to an increase in ApoB secretion. Given that, in our model, ApoB secretion is diminished upon MCP-1 treatment in Huh-7 cells and that this phenomenon can be rescued by an ERK inhibitor, we hypothesize that lipid accumulation is partly due to a blockade of lipid secretion via the ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK has already been shown to be induced by MCP-1 in Chinese hamster ovary cells and in smooth muscle cells 22 , and to be involved in MCP-1-mediated monocyte chemotaxis. 34 Interestingly, Tsai et al 21 have recently demonstrated that inhibition of ERK pathway in HepG2 cells led to an increase in ApoB secretion. Given that, in our model, ApoB secretion is diminished upon MCP-1 treatment in Huh-7 cells and that this phenomenon can be rescued by an ERK inhibitor, we hypothesize that lipid accumulation is partly due to a blockade of lipid secretion via the ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the involvement of ERK in lipid secretion has been reported in HepG2 cells. 21 In addition, MCP-1 has been shown to activate MAPK pathways. 22,23 To determine whether MCP-1-induced lipid accumulation was dependent on MAPK pathway activation, even in the absence of large amounts of CCR2, Huh-7 cells were treated with MCP-1 and PD98059, an ERK inhibitor, or SB203580, a p38 MAPK inhibitor (Fig.…”
Section: Of Human Scwat Explants Induces Significantmentioning
confidence: 99%
“…In cultured hepatocytes, levels of DGAT1 and DGAT2 mRNA are regulated by the MEK-ERK signaling pathway (95). Inhibition of this signaling pathway in HepG2 hepatoma cells increased DGAT1 and DGAT2 mRNA levels 2-and 4-fold, respectively, and stimulated VLDL secretion.…”
Section: Regulation Of Dgat Enzymesmentioning
confidence: 99%
“…In contrast, MAPK family members such as ERK exert protective and anti-apoptotic effects upon activation by an upstream kinase and regulate a number of major cellular functions, such as cell proliferation, differentiation and inflammation (Czaja et al, 2003). Furthermore, ERK activation is reported to decrease DGAT2 expression (Wang et al, 2010;Tsai et al, 2007). Increased JNK phosphorylation has been reported in steatosis and NASH model mice (Hirosumi et al, 2002).…”
mentioning
confidence: 99%